Catalyst for electrochemical catalytic reduction of nitrate as well as preparation method and application of catalyst
By using copper and rhodium metal catalysts on carbon substrates, the problems of N-N coupling reactions are difficult, low NH3 yield and toxic intermediates during the electrochemical catalytic reduction of nitrates, and efficient NO3-reduction and NH3 yield are achieved.
Patent Information
- Application Number
- CN202510024772.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-05-02
AI Technical Summary
During the electrochemical catalytic reduction of nitrate, there are problems such as the difficulty of N-N coupling reaction, low NH3 yield, the generation of nitrites, the low NO3-conversion efficiency.
Using a catalyst including a carbon substrate and copper and/or rhodium metal anchored on the carbon substrate, prepared by baking of imidazole organic compounds and surfactants, the metals exist in the form of clusters of metal monoatoms and metal atoms, and copper and rhodium act together to improve catalytic performance.
The catalyst's selection rate for NH4+ and NO2- is improved, the yield of NH3 is increased, and the NO3-reduction efficiency is maintained, and it performs well at high potentials.
Smart Images

Figure BDA0005232484070000091 
Figure BDA0005232484070000101 
Figure HDA0005232484090000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a catalyst that can be used for electrochemical catalytic reduction of nitrates, and a preparation method and application thereof. Background Art
[0002] As an industrial and agricultural pollutant, nitrates are extremely harmful to the environment and humans. Nitrates come from wastewater treatment plants, fertilized farmland, faulty septic systems, animal manure storage facilities, and industrial discharges. Agricultural and urban nitrogen are the main causes of water pollution. The large-scale use of nitrogen fertilizers is one of the main causes of excessive nitrates in water bodies, which directly leads to eutrophication and other environmental problems. Nitrates entering drinking water can cause serious health problems. For example, excessive intake of nitrates can cause people to suffer from methemoglobinemia and cancer.
[0003] Ammonia (NH3) is an important basic chemical raw material for the chemical industry and is also the next generation of hydrogen-rich fuel. At present, the industrial production method of NH3 is the Haber-Bosch process, which uses N2 and H2 as raw materials and catalyzes the reaction with iron-based materials. However, the Haber-Bosch process relies on high temperature and high pressure reaction conditions (400-500℃, 100-200atm), consumes 1% of the world's annual energy output, releases a large amount of greenhouse gases, and causes harm to the environment.
[0004] Reducing harmful nitrates in wastewater into an important chemical raw material, ammonia (NH3), has been a research hotspot in recent years. - ) There are three main methods for wastewater remediation: biological, physical and electrocatalytic, which aim to convert nitrate into harmless products. Biological method is the most widespread and technologically mature method, but pathogenic bacteria in drinking water are a serious problem of biological consumption. Physical methods include reverse osmosis, electrocoagulation, electrodialysis and ion exchange, which are usually used for drinking water treatment, but the generation of wastewater containing secondary nitrates during the treatment process is inevitable. Compared with these methods, the use of catalysts for electrocatalytic reduction of NO3 - (NO3RR) does not produce secondary waste streams and has the advantages of mild operating conditions and reusable catalysts.
[0005] In the process of electrochemical catalytic nitrate reduction, the following problems are faced: 1. The NN coupling reaction is difficult; 2. There is NH4 + / NH3 and hydrogen evolution reaction kinetic competition, resulting in low NH3 yield; 3, NO3 - It is difficult to completely reduce it to NH4 + , N2 and other non-polluting products, and the toxic intermediate product nitrite (NO2- );4. Low NO3 - Conversion efficiency.
[0006] Therefore, in order to solve the above problems, it is necessary to find an efficient catalyst. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a catalyst for electrochemical catalytic reduction of nitrate, a preparation method and application thereof. The catalyst for electrochemical catalytic reduction of nitrate provided by the present invention has a high selectivity for the product and maintains a high NO3 - Reduction efficiency.
[0008] In a first aspect, the present invention provides a catalyst that can be used for the electrochemical catalytic reduction of nitrate ions, comprising a carbon substrate and a metal anchored on the carbon substrate, wherein the metal exists in the form of metal single atoms and metal atom clusters, and the metal comprises copper and / or rhodium.
[0009] Precious metals such as Pt, Rh, Ir, Rh, Au and Ag all show extremely high electrochemical performance in the electrocatalytic reduction of nitrate, and the reduction activity of platinum group metals is Rh>Ru>Ir>Pt. Cu is NO3 in neutral and alkaline water environments. - As one of the non-precious metals with the best reduction activity, Cu can well promote the rate-determining step of nitrate reduction (NO3 - →NO2 - ).
[0010] In some embodiments, the metal includes copper and rhodium. The inventors of the present application have found that when the metal includes both copper and rhodium, the synergistic effect of copper and rhodium can improve the catalyst's NH4 + and NO2 - selectivity and at the same time increase the yield of NH3.
[0011] In some embodiments, the carbon substrate is obtained by calcining an imidazole organic compound and a surfactant. The imidazole organic compound is selected from any one or more of 2-methylimidazole, 1,2-dimethylimidazole or 1,3-dimethylimidazole. The surfactant is selected from any one or more of a cationic surfactant, an anionic surfactant, an organic acid or an organic base; preferably, the surfactant is selected from any one or more of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, sodium polystyrene sulfonate, tetradecylammonium bromide, citric acid or ascorbic acid.
[0012] In some embodiments, in the catalyst, the mass percentage of the metal is 0.5-5%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.92%, 0.94%, 0.96%, 0.98%, 1%, 1.2%, 1.5%, 2%, 3%, 4%, 5% or any value therebetween.
[0013] In some embodiments, in the catalyst, the mass proportion of the metal is 0.9-1%.
[0014] In some embodiments, in the catalyst, based on the total mass of copper and rhodium, the mass proportion of copper is 0-100%, and the mass proportion of rhodium is 0-100%.
[0015] In some embodiments, in the catalyst, based on the total mass of copper and rhodium, the mass proportion of copper is 80-99%, for example, 80%, 85%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or any value therebetween.
[0016] In some embodiments, in the catalyst, the mass proportion of rhodium element is 1-20% based on the total mass of copper element and rhodium element; for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20% or any value therebetween.
[0017] In some embodiments, in the catalyst, based on the total mass of copper and rhodium, the mass proportion of copper is 90-99%, and the mass proportion of rhodium is 1-10%.
[0018] In some embodiments, the catalyst further comprises zinc. Zinc exists in single atomic form.
[0019] In some embodiments, in the catalyst, the mass proportion of zinc element is 3-10%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween.
[0020] In some embodiments, in the catalyst, the mass proportion of zinc element is 3-5%.
[0021] In some embodiments, the catalyst may be represented by Cu x R y / C, where x and y represent the mass content ratio of the elements.
[0022] In some embodiments, based on the total mass of the copper element and the rhodium element, x and y are each independently 0-100%.
[0023] In some embodiments, based on the total mass of the copper element and the rhodium element, x is 80-99% and y is 1-20%.
[0024] In some embodiments, based on the total mass of the copper element and the rhodium element, x is 90-99% and y is 1-10%.
[0025] In a second aspect, the present invention provides a method for preparing a catalyst that can be used for electrochemical catalytic reduction of nitrate, comprising the following steps:
[0026] (1) mixing an imidazole organic compound, a surfactant, a metal salt, a zinc salt and a solvent to obtain a solution; wherein the metal salt comprises a copper salt and / or a rhodium salt;
[0027] (2) The solution is subjected to solid-liquid separation, and the obtained solid is roasted under an inert atmosphere.
[0028] In some embodiments, the metal salts include copper salts and rhodium salts.
[0029] In some embodiments, the imidazole organic compound is selected from any one or more of 2-methylimidazole, 1,2-dimethylimidazole or 1,3-dimethylimidazole.
[0030] In some embodiments, the surfactant is selected from any one or more of a cationic surfactant, an anionic surfactant, an organic acid, and an organic base.
[0031] In some embodiments, the surfactant is selected from any one or more of polyvinyl pyrrolidone, sodium polystyrene sulfonate, tetradecyl ammonium bromide, hexadecyl trimethyl ammonium bromide, citric acid or ascorbic acid.
[0032] In some embodiments, the copper salt is selected from one or more of copper nitrate, copper sulfate or copper chloride.
[0033] In some embodiments, the rhodium salt is selected from rhodium chloride and / or rhodium sulfate.
[0034] In some embodiments, the zinc salt is selected from one or more of zinc nitrate, zinc sulfate, or zinc chloride.
[0035] In some embodiments, the solvent is selected from deionized water.
[0036] In some embodiments, the amount of the surfactant is 0.1-0.5% by mass of the imidazole organic compound, for example, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2% or any value therebetween, preferably 0.1-0.2%.
[0037] In some embodiments, the molar ratio of the zinc salt to the metal salt is (70-100):1, for example, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1 or any value therebetween, preferably (75-90):1.
[0038] In some embodiments, when the metal salt includes a copper salt and a rhodium salt, the molar ratio of the zinc salt to the copper salt is (70-100):1, for example, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1 or any value therebetween, preferably (75-90):1.
[0039] In some embodiments, the molar ratio of the rhodium salt to the copper salt is (0.1-0.5):1, for example, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1 or any value therebetween, preferably (0.1-0.3):1.
[0040] In some embodiments, the inert atmosphere is selected from argon.
[0041] In some embodiments, the heating rate of the calcination is 2-10°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value therebetween.
[0042] In some embodiments, the heating rate of the calcination is 3-8°C / min.
[0043] In some embodiments, the calcination temperature is 800-1200°C, for example, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or any value therebetween.
[0044] In some embodiments, the calcination temperature is 900-1100° C. In order to graphitize the carbon material, the calcination is preferably performed at the above temperature.
[0045] In some embodiments, the preparation method comprises:
[0046] (1) mixing an imidazole organic compound, a surfactant and a solvent to obtain a solution A;
[0047] (2) mixing a zinc salt, a metal salt and a solvent to obtain a solution B; wherein the metal salt comprises a copper salt and / or a rhodium salt, and preferably, the metal salt comprises a copper salt and a rhodium salt;
[0048] (3) mixing solution A and solution B to obtain a mixed solution;
[0049] (4) The mixed solution is subjected to solid-liquid separation, and the obtained solid is roasted under an inert atmosphere.
[0050] In some embodiments, the solid-liquid separation can be performed by centrifugation, filtration, etc.
[0051] In a third aspect, the present invention provides a catalyst for electrochemical catalytic reduction of nitrate according to the first aspect or a catalyst for electrochemical catalytic reduction of nitrate obtained by the preparation method according to the second aspect in the electrochemical catalytic reduction of NO3 - Application in reduction to produce NH3.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The catalyst of the present invention has good electrochemical catalytic reduction performance of nitrate at high potential: NO3 - The conversion rate is kept at a high level, NH4 + The selectivity of NH4 was also good at high potential. + The rate exceeds that of other catalysts of the same type.
[0054] (2) The catalyst of the present invention uses very low amounts of metal, which greatly improves atomic utilization and is conducive to mass production and application.
[0055] (3) The preparation method of the present invention is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 Scanning electron microscope images at different magnifications;
[0057] Figure 2 High-resolution transmission electron microscope images at different magnifications;
[0058] Figure 3 is the HAADF-STEM image of Example 1;
[0059] Figure 4 is the X-ray diffraction pattern of the catalyst obtained in Example 1-4;
[0060] Figure 5 It is a high-angle annular dark-field scanning transmission electron microscope image of Example 1 and the corresponding distribution diagram of Cu, Rh, C, N and O;
[0061] Figure 6 (a) is the catalyst of Example 1 at different potentials NO3 -Conversion rate diagram; (b) is the catalyst of Example 1 at different potentials NH4 + 、NO2 - The selectivity graph of
[0062] Figure 7 The yield of NH3 of the catalyst of Example 1 at different potentials;
[0063] Figure 8 It is the X-ray diffraction pattern of comparative example 1, comparative example 2, and comparative example 3;
[0064] Fig. 9 The high-resolution transmission electron microscope images at different magnifications of Example 3 are shown;
[0065] Fig.10 High-resolution transmission electron microscope images at different magnifications of Comparative Example 1;
[0066] Fig.11 High-resolution transmission electron microscope images at different magnifications of Comparative Example 2;
[0067] Fig.12 High-resolution transmission electron microscope images of Comparative Example 3 at different magnifications. DETAILED DESCRIPTION
[0068] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0069] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0070] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0071] The "cluster" in the present invention refers to a relatively stable microscopic or submicroscopic aggregate composed of several or even thousands of atoms, molecules or ions through physical or chemical binding forces, and its physical and chemical properties vary with the number of atoms contained. Cluster is a concept of material scale nanomaterials. Cluster can be regarded as a new level of material structure between atoms, molecules and macroscopic solid substances, and is a transitional state of various substances from atoms and molecules to bulk substances.
[0072] Example 1
[0073] Preparation of Cu 97.5 R 2.5 / C:
[0074] Take a beaker A, weigh 10.8372g 2-methylimidazole, 19.68mg hexadecyltrimethylammonium bromide (CTAB), add the two to beaker A in turn, then add 100mL deionized water, and stir magnetically for 30min. Take another beaker B, weigh 2.4mmol zinc nitrate, 0.03mmol copper nitrate, 0.006mmol rhodium chloride, add the three in turn, then add 100mL deionized water, and stir magnetically for 30min. Add solution B to solution A and stir for 10min (400rpm). After standing for 3h, place it in a centrifuge and centrifuge it at 8000rpm for 5min. After centrifugation, pour off the supernatant, wash twice with methanol, and freeze-dry. Pass argon into a tubular furnace at a rate of 5℃ / min, keep warm at 1000℃ for 3h, and obtain the finished catalyst after cooling.
[0075] from Figure 1 The scanning electron microscope image in the figure shows that the catalyst is in the shape of a block with a side length of about 100 nm. Figure 2 No lattice fringes can be observed in medium and high resolution transmission electron microscopy images, indicating that it is an amorphous carbon material. Figure 3 The high-angle annular dark field scanning transmission mode of the spherical aberration electron microscope can observe multiple large bright spots (red circles) and single bright spots (yellow circles) distributed in the large bright spots, indicating that copper and rhodium exist on the surface of the carbon substrate in the form of atomic clusters and single atoms. Figure 4 In the XRD spectrum, the peak at 2θ = 22° corresponds to the (002) crystal plane of carbon, indicating its amorphous carbon structure, which is consistent with the high-resolution transmission electron microscopy image ( Figure 2 ). Figure 5 From the high-angle annular dark-field scanning transmission electron microscope image and the element distribution map, it can be seen that copper and rhodium elements are evenly distributed, proving the successful incorporation of copper and rhodium elements.
[0076] Figure 6a The results show that the catalyst sample obtained in Example 1 has a voltage range of -0.8V to -1.2V, NO3 - The conversion rate gradually increased, reaching a maximum at -1.1V, and then slightly decreased as the applied potential continued to increase. At voltages of -1.0V, -1.1V, and -1.2V, the conversion rate reached more than 90%, which indicates that Cu 97.5 R 2.5 / C has good catalytic performance under high voltage. Figure 6 b shows the Cu 97.5 R 2.5 / C for NH4 + 、NO2 - As can be seen from the figure, as the applied potential gradually increases, Cu 97.5 R 2.5 / C for NO2 - The selectivity of Cu decreases gradually, reaching the lowest value at -1.0V, and then the selectivity remains almost unchanged as the potential continues to increase. 97.5 R 2.5 / C for NH4 + The selectivity increases with the increase of applied potential, reaching a maximum of 81.03% at -1.0V, and then the selectivity decreases as the applied potential increases, and increases again at -1.2V, almost the same as at -1.0V. This shows that Cu 97.5 R 2.5 / C at high potential for NH4 + The selectivity can be maintained at a high level, and for NO2 - The selection rate remains at a low level.
[0077] Figure 7 The results show the yield of NH3 in the voltage range of -0.8V to -1.2V for the catalyst obtained in Example 1. It can be seen that in the case of Cu 97.5 R 2.5 In / C, the NH3 yield increases as the applied potential shifts negatively from -0.8 V and reaches a maximum of 1252.22 μg·h at -1.1 V. -1 mg -1 , and then slightly decreases with the continued increase of the applied potential. This may be because the more negative applied potential promotes the competitive hydrogen evolution reaction, thereby reducing the yield of NH3.
[0078] The element ratio of the catalyst was determined by inductively coupled plasma emission spectroscopy (ICP). 97.5 R 2.5The mass fraction of copper Cu in / C is 0.925wt.%, the mass fraction of rhodium Rh is 0.0236wt.%, and the mass fraction of zinc Zn is 4.06wt.%, wherein the mass contents of Cu and Rh based on the total mass of copper and rhodium are as shown in Table 1.
[0079] Example 2
[0080] Preparation of Cu 91.5 R 8.5 / C:
[0081] Take a beaker A, weigh 10.8372g 2-methylimidazole, 19.68mg hexadecyltrimethylammonium bromide (CTAB), add the two to beaker A in turn, then add 100mL deionized water, and stir magnetically for 30min. Take another beaker B, weigh 2.4mmol zinc nitrate, 0.03mmol copper nitrate, 0.012mmol rhodium chloride, add the three in turn, then add 100mL deionized water, and stir magnetically for 30min. Add solution B to solution A and stir for 10min (400rpm). After standing for 3h, place it in a centrifuge and centrifuge at 8000rpm for 5min. After centrifugation, pour off the supernatant, wash twice with methanol, and freeze-dry. Pass argon into a tubular furnace at a rate of 5℃ / min, keep warm at 1000℃ for 3h, and obtain the finished catalyst after cooling. The XRD of the finished catalyst is as follows Figure 4 As shown, the peak at 2θ=22° corresponds to the (002) crystal plane of carbon, indicating its amorphous carbon structure.
[0082] Example 3
[0083] Preparation of Cu 97.65 R 2.35 / C-800℃:
[0084] Take a beaker A, weigh 10.8372g 2-methylimidazole, 19.68mg hexadecyltrimethylammonium bromide (CTAB), add the two to beaker A in turn, then add 100mL deionized water, and stir magnetically for 30min. Take another beaker B, weigh 2.4mmol zinc nitrate, 0.03mmol copper nitrate, 0.006mmol rhodium chloride, add the three in turn, then add 100mL deionized water, and stir magnetically for 30min. Add solution B to solution A and stir for 10min (400rpm). After standing for 3h, place it in a centrifuge and centrifuge at 8000rpm for 5min. After centrifugation, pour off the supernatant, wash twice with methanol, and freeze-dry. Pass argon into a tubular furnace at a rate of 5℃ / min, keep warm at 800℃ for 3h, and obtain the finished catalyst after cooling. The XRD of the finished catalyst is as follows Figure 4 The TEM of the finished catalyst is shown in Fig. 9As shown. This indicates that the catalyst has an amorphous carbon structure.
[0085] Example 4
[0086] Preparation of Cu 100 / C:
[0087] Different from Example 2, rhodium chloride is not added, specifically comprising:
[0088] Take a beaker A, weigh 10.8372g 2-methylimidazole and 19.68mg hexadecyltrimethylammonium bromide (CTAB), add the two to beaker A in turn, then add 100mL deionized water, and stir magnetically for 30 minutes. Take another beaker B, weigh 2.4mmol zinc nitrate and 0.03mmol copper nitrate, add the three in turn, then add 100mL deionized water, and stir magnetically for 30 minutes. Add solution B to solution A and stir for 10min (400rpm). After standing for 3h, place it in a centrifuge, centrifuge at 8000rpm for 5min. After centrifugation, pour off the supernatant, wash twice with methanol, and freeze-dry. Pass argon into a tubular furnace at a rate of 5℃ / min, keep warm at 1000℃ for 3h, and obtain the finished catalyst after cooling. The XRD of the finished catalyst is as follows Figure 4 As shown. This indicates that the catalyst has an amorphous carbon structure.
[0089] Comparative Example 1
[0090] Preparation of Ni 81.4 R 18.6 / C:
[0091] Take a beaker A, weigh 10.8372g 2-methylimidazole, 19.68mg hexadecyltrimethylammonium bromide (CTAB), add the two to beaker A in turn, then add 100mL deionized water, and stir magnetically for 30min. Take another beaker B, weigh 2.4mmol zinc nitrate, 0.03mmol nickel nitrate, 0.006mmol rhodium chloride, add the three in turn, then add 100mL deionized water, and stir magnetically for 30min. Add solution B to solution A and stir for 10min (400rpm). After standing for 3h, place it in a centrifuge and centrifuge at 8000rpm for 5min. After centrifugation, pour off the supernatant, wash twice with methanol, and freeze-dry. Pass argon into a tubular furnace at a rate of 5℃ / min, keep warm at 1000℃ for 3h, and obtain the finished catalyst after cooling. The XRD of the finished catalyst is as follows Figure 8 The TEM of the finished catalyst is shown in Fig.10 As shown. Figure 8 and Fig.10 It can be seen that the catalyst of Comparative Example 1 contains an amorphous carbon structure.
[0092] The element ratio of the catalyst in Comparative Example 1 was determined by inductively coupled plasma emission spectroscopy (ICP), wherein the mass contents of Ni and Rh, based on the total mass of nickel and rhodium, are shown in Table 2.
[0093] Comparative Example 2
[0094] Preparation of Co 93.95 R 6.05 / C:
[0095] Take a beaker A, weigh 10.8372g 2-methylimidazole, 19.68mg hexadecyltrimethylammonium bromide (CTAB), add the two to beaker A in turn, then add 100mL deionized water, and stir magnetically for 30min. Take another beaker B, weigh 2.4mmol zinc nitrate, 0.03mmol cobalt nitrate, 0.006mmol rhodium chloride, add the three in turn, then add 100mL deionized water, and stir magnetically for 30min. Add solution B to solution A and stir for 10min (400rpm). After standing for 3h, place it in a centrifuge, centrifuge at 8000rpm for 5min. After centrifugation, pour off the supernatant, wash twice with methanol, and freeze-dry. Pass argon into a tubular furnace at a rate of 5℃ / min, keep warm at 1000℃ for 3h, and obtain the finished catalyst after cooling. The XRD of the finished catalyst is as follows Figure 8 The TEM of the finished catalyst is shown in Fig.11 As shown. Figure 8 and Fig.11 It can be seen that the catalyst of Comparative Example 2 contains an amorphous carbon structure.
[0096] The element ratio of the catalyst in Comparative Example 2 was determined by inductively coupled plasma emission spectroscopy (ICP), wherein the mass contents of Co and Rh, based on the total mass of cobalt and rhodium, are shown in Table 2.
[0097] Comparative Example 3
[0098] Preparation of Cu 93.2 Pt 6.8 / C:
[0099] Take a beaker A, weigh 10.8372g 2-methylimidazole, 19.68mg hexadecyltrimethylammonium bromide (CTAB), add the two to beaker A in turn, then add 100mL deionized water, and stir magnetically for 30min. Take another beaker B, weigh 2.4mmol zinc nitrate, 0.03mmol copper nitrate, 0.006mmol hexahydroxyhydroplatinic acid, add the three in turn, then add 100mL deionized water, and stir magnetically for 30min. Add solution B to solution A and stir for 10min (400rpm). After standing for 3h, place it in a centrifuge and centrifuge at 8000rpm for 5min. After centrifugation, pour off the supernatant, wash twice with methanol, and freeze-dry. Pass argon into a tubular furnace at a rate of 5℃ / min, keep warm at 1000℃ for 3h, and obtain the finished catalyst after cooling. The XRD of the finished catalyst is as follows Figure 8 The TEM of the finished catalyst is shown in Fig.12 As shown. Figure 8 and Fig.12 It can be seen that the catalyst of Comparative Example 3 contains an amorphous carbon structure.
[0100] Inductively coupled plasma emission spectroscopy (ICP) was performed on Comparative Example 3 to determine the element ratio of the catalyst, wherein the mass contents of Cu and Pt, based on the total mass of copper and platinum, are shown in Table 2.
[0101] Table 1
[0102] sample Cu(wt.%) Rh(wt.%) Example 1 97.5 2.5 Example 2 91.5 8.5 Example 3 97.65 2.35 Example 4 100 0
[0103] In Table 1, Cu (wt.%) and Rh (wt.%) are the mass percentages calculated based on the total mass of copper and rhodium.
[0104] Table 2
[0105]
[0106] The mass fractions of the elements in Table 2 are all calculated based on the total mass of nickel and rhodium, or the total mass of cobalt and rhodium, or the total mass of copper and platinum.
[0107] The electrochemical catalytic nitrate reduction test was carried out on the catalysts prepared in the examples and comparative examples. The results are shown in Table 3.
[0108] The method for testing the electrochemical catalytic nitrate reduction is as follows:
[0109] H-type electrolytic cell
[0110] Cathode cell: 50ppmNaNO3-N+0.1MNaOH+0.1MNa2SO4
[0111] Anode cell: 0.1MNaOH+0.1MNa2SO4
[0112] Reference electrode: Mercury oxide electrode (Hg / HgO)
[0113] Working electrode: Catalyst loaded on carbon paper with an area of 1*2mm
[0114] Counter electrode: platinum (Pt), area 2*2mm.
[0115] Table 3
[0116]
[0117] It can be seen from Table 3 that, compared with Comparative Examples 1-3, the catalyst of the present invention has a higher NH3 yield.
[0118] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for electrochemical catalytic reduction of nitrate, comprising a carbon substrate and a metal anchored on the carbon substrate, wherein: The metal exists in the form of metal single atoms and metal atom clusters, and the metal includes copper and / or rhodium; Preferably, the metals include copper and rhodium.
2. The catalyst according to claim 1, characterized in that In the catalyst, the mass proportion of the metal is 0.5-5%, preferably 0.9-1%.
3. The catalyst according to claim 1 or 2, characterized in that When the metal includes copper and rhodium, in the catalyst, based on the total mass of copper and rhodium, the mass of copper accounts for 0-100%, and the mass of rhodium accounts for 0-100%; Preferably, when the metal includes copper and rhodium, in the catalyst, based on the total mass of copper and rhodium, the mass proportion of copper is 80-99%, and the mass proportion of rhodium is 1-20%; Preferably, when the metal includes copper and rhodium, in the catalyst, based on the total mass of copper and rhodium, the mass proportion of copper is 90-99%, and the mass proportion of rhodium is 1-10%.
4. The catalyst according to any one of claims 1 to 3, characterized in that The catalyst also includes zinc; Preferably, in the catalyst, the mass proportion of zinc element is 3-10%, preferably 3-5%.
5. A method for preparing a catalyst for electrochemical catalytic reduction of nitrate, comprising the following steps: (1) mixing an imidazole organic compound, a surfactant, a metal salt, a zinc salt and a solvent to obtain a solution; wherein: The metal salt comprises a copper salt and / or a rhodium salt, preferably, the metal salt comprises a copper salt and a rhodium salt; (2) The solution is subjected to solid-liquid separation, and the obtained solid is roasted under an inert atmosphere.
6. The preparation method according to claim 5, characterized in that: The imidazole organic compound is selected from any one or more of 2-methylimidazole, 1,2-dimethylimidazole or 1,3-dimethylimidazole; and / or The surfactant is selected from any one or more of a cationic surfactant, an anionic surfactant, an organic acid or an organic base; Preferably, the surfactant is selected from any one or more of cetyltrimethylammonium bromide, polyvinylpyrrolidone, sodium polystyrene sulfonate, tetradecylammonium bromide, citric acid, and ascorbic acid; and / or The copper salt is selected from one or more of copper nitrate, copper sulfate or copper chloride; and / or The rhodium salt is selected from chloride and / or sulfate of rhodium; and / or The zinc salt is selected from one or more of zinc nitrate, zinc sulfate or zinc chloride; and / or The solvent is selected from deionized water.
7. The preparation method according to claim 5 or 6, characterized in that: The amount of the surfactant is 0.1-0.5% by mass of the imidazole organic compound, preferably 0.1-0.2%; and / or The molar ratio of the zinc salt to the metal salt is (70-100):1, preferably (75-90):1; and / or When the metal salt comprises a copper salt and a rhodium salt, the molar ratio of the zinc salt to the copper salt is (70-100):1, preferably (75-90):1; and / or The molar ratio of the rhodium salt to the copper salt is (0.1-0.5):1, preferably (0.1-0.3):
1.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The inert atmosphere is selected from argon; and / or The heating rate of the calcination is 2-10°C / min, preferably 3-8°C / min; and / or The calcination temperature is 800-1200°C, preferably 900-1100°C.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method comprises: (1) mixing an imidazole organic compound, a surfactant and a solvent to obtain a solution A; (2) mixing a zinc salt, a metal salt and a solvent to obtain a solution B; wherein the metal salt comprises a copper salt and / or a rhodium salt, and preferably, the metal salt comprises a copper salt and a rhodium salt; (3) mixing solution A and solution B to obtain a mixed solution; (4) The mixed solution is subjected to solid-liquid separation, and the obtained solid is roasted under an inert atmosphere.
10. A catalyst for electrochemical catalytic reduction of nitrate according to any one of claims 1 to 4 or a catalyst for electrochemical catalytic reduction of nitrate obtained by the preparation method according to any one of claims 5 to 9 in electrochemical catalytic reduction of NO3 - Application in reduction to produce NH3.